2014
DOI: 10.1111/cas.12389
|View full text |Cite
|
Sign up to set email alerts
|

Gene expression profiling of Epstein–Barr virus‐positive diffuse large B‐cell lymphoma of the elderly reveals alterations of characteristic oncogenetic pathways

Abstract: Epstein–Barr virus (EBV)-positive diffuse large B-cell lymphoma (DLBCL) of the elderly (EBV[+]DLBCL-E) is classified as a subtype of DLBCL. Until now, its molecular pathogenesis has remained unknown. To identify pathways characteristic of EBV(+)DLBCL-E, gene expression profiling of five EBV(+)DLBCL-E and seven EBV-negative DLBCL (EBV[−]DLBCL) cases was undertaken using human oligonucleotide microarray analysis. Gene set enrichment analysis and gene ontology analysis showed that gene sets of the Janus kinase-si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
70
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 63 publications
(72 citation statements)
references
References 46 publications
(124 reference statements)
2
70
0
Order By: Relevance
“…Over half of tumors demonstrated nuclear expression of both canonical and alternative NFκB pathways, significantly greater NFκB activity than that seen in ABC lymphoma alone. Furthermore, Kato et al (2014) found that infecting human ABC DLBCL-derived cell lines with EBV enhanced NFκB activity measured by electrophoretic mobility shift assay.…”
Section: Biologymentioning
confidence: 99%
See 2 more Smart Citations
“…Over half of tumors demonstrated nuclear expression of both canonical and alternative NFκB pathways, significantly greater NFκB activity than that seen in ABC lymphoma alone. Furthermore, Kato et al (2014) found that infecting human ABC DLBCL-derived cell lines with EBV enhanced NFκB activity measured by electrophoretic mobility shift assay.…”
Section: Biologymentioning
confidence: 99%
“…Age, by itself, is a risk for poorer outcomes in DLBCL. However, EBV-positive DLBCL is also associated with an ABC GEP, which is known to have a worse outcome than GCB tumors (Kato et al 2014;Ok et al 2014). Montes-Moreno et al (2012) explored whether the difference in survival was merely due to a higher prevalence of ABC phenotype.…”
Section: Clinical Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…12-14 Most cases of DLBCL-E show activation of nuclear factor-kB pathway, 11,[15][16][17] most likely promoted by EBV through latent membrane protein 1 (LMP1) 18,19 and less likely by MYD88, CD79B, and CARD11 gene mutations. 20 Furthermore, gene expression profiling shows an enrichment of Janus kinasesignal transducer and activator of transcription-related genes (JAK/STAT), immune/inflammatory-related genes, and genes involved in cell-cycle progression and cellular metabolism.…”
Section: Introductionmentioning
confidence: 99%
“…20 Furthermore, gene expression profiling shows an enrichment of Janus kinasesignal transducer and activator of transcription-related genes (JAK/STAT), immune/inflammatory-related genes, and genes involved in cell-cycle progression and cellular metabolism. 15,16 Recent studies using high-resolution array comparative genomic hybridization reported cytogenetic abnormalities shared among DLBCL-E, plasmablastic lymphoma, posttransplant lymphoproliferative disorders and EBV-negative DLBCL-not otherwise specified (DLBCL-NOS). 20 Lack of uniform criteria (eg, age cutoff, percentage of EBV 1 tumor cells required for diagnosis, morphologic heterogeneity) may account for reported differences in disease prevalence and prognostic features.…”
Section: Introductionmentioning
confidence: 99%